Roentgenographic Evaluation of the Spine in Patients With Osteogenesis Imperfecta. Issue 47 (November 2015) - de Lima, Marcos Vaz; de Lima, Fabiana Vaz; Akkari, Miguel; Resende, Vanessa Ribeiro de; Santili, Claudio
Abstract : Abstract: Osteogenesis imperfecta (OI) is a hereditary connective tissue disorder that leads to bone weakness and deformities, especially in the spine, which can lead to poor outcomes. The aim of this study was to find patterns and risk factors in spinal deformities in patients with OI. In a retrospective study, 70 patients with OI were selected. Radiographs of the spine were evaluated. We observed the presence or absence of the following changes: biconcave vertebrae, chest and vertebral deformities, unilateral rib, and thoracolumbar kyphosis. The greater curve was considered the primary one, and the secondary curve considered compensatory. In the study sample, we observed that the patients' ages ranged between 7 and 50 years, with a mean equal to 13 years, and 76% had scoliosis. In 68% of cases the main curve in the thoracic region was observed with the convexity to the right. The following was found in patients with OI: scoliosis, biconcave vertebrae, vertebral and chest deformity, unilateral rib, and thoracolumbar kyphosis. The thoracolumbar kyphosis is highly associated with thoracic hypokyphosis in patients with OI.